HISTOPATHOLOGICAL PATTERNS AND CLINICOPATHOLOGIC CORRELATES OF NON-ALCOHOLIC STEATOHEPATITIS IN INDIAN ADULTS (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Non-alcoholic fatty liver disease (NAFLD) is increasingly common worldwide, with a substantial proportion progressing to non-alcoholic steatohepatitis (NASH) and fibrosis. In India, metabolic risk factors are rising, and biopsy studies suggest that over 60% of NAFLD patients have NASH, with ~30–35% showing advanced fibrosis. Histologic diagnosis of NASH (macrovesicular steatosis, ballooning degeneration, and inflammation) is the gold standard. We examined liver biopsy samples from Indian adults with NAFLD to characterize histopathological patterns and correlate these with clinical features. Materials and Methods: We conducted a retrospective analysis of 150 adult patients with biopsy-proven NAFLD (exclusion of other etiologies) at a tertiary center in India. Liver biopsies were scored by standard criteria (Brunt et al.) for steatosis grade (1–3), lobular inflammation (0–3), hepatocyte ballooning (0–2), portal inflammation (0–3), and fibrosis stage (0–4). NASH diagnosis required steatosis ≥5%, ballooning, and lobular inflammation. Clinical data (age, gender, BMI, diabetes, hypertension, metabolic syndrome, liver enzymes) were recorded. Continuous variables were compared by t-test or Mann–Whitney U test and categorical by chi-square. Logistic regression identified factors independently associated with NASH. Statistical significance was set at p